2000
DOI: 10.1176/jnp.12.4.451
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Among Apathy, Depression, and Cognitive Impairment in HIV/AIDS

Abstract: This study was designed to determine whether apathy is associated with neurocognitive symptoms and/or depressive symptoms in HIV/AIDS and also whether apathy is associated with patient expectancies about antiretroviral medication adherence. Seventy-five HIV+ homosexual men and 58 HIV+ women were assessed for depressive disorders and symptoms. Neuropsychological tests measured attention, concentration, learning, memory, executive function, and psychomotor speed. Other measures included Marin's Apathy Evaluation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
35
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 22 publications
9
35
0
1
Order By: Relevance
“…Persistent and pronounced apathy occurs with surprising frequency among HIV+ patients [29,30]. Although apathy is often mistakenly considered solely a symptom of a depressive disorder, research in HIV/AIDS as well as other neurological diseases has shown that apathy can reliably be discriminated from depression, and can exist independent of a depressive syndrome [31,32].…”
Section: Other Neuropsychiatric Disordersmentioning
confidence: 99%
“…Persistent and pronounced apathy occurs with surprising frequency among HIV+ patients [29,30]. Although apathy is often mistakenly considered solely a symptom of a depressive disorder, research in HIV/AIDS as well as other neurological diseases has shown that apathy can reliably be discriminated from depression, and can exist independent of a depressive syndrome [31,32].…”
Section: Other Neuropsychiatric Disordersmentioning
confidence: 99%
“…It is possible that depression and anxiety symptomatology may relate to other neural systems affected by HIV that were not measured in the current study, although other work evaluating primary neuropsychological domains have thus far not found that to be the case (Castellon et al, 1998;Grant et al, 1993;Hinkin et al, 1992;Mapou et al, 1993;Perdices et al, 1992;Rabkin et al, 2000). Alternatively, these psychiatric features may be more related to psychological and psychosocial factors (Perdices et al, 1992).…”
Section: Discussionmentioning
confidence: 75%
“…Castellon et al (1998) found prominent symptoms of apathy to be associated with working memory deficits in HIV-positive individuals and, in a second study, found that prominent irritability and apathy were highly related to poorer performance on those neuropsychological tasks most dependent upon executive functioning . In contrast, Rabkin et al (2000) found that apathy was not related to performances across several neuropsychological domains, including frontal systems, in HIVseropositive (HIV+) individuals. The authors concluded that the absence of a significant relationship between cognition and apathy indicated that apathy may not represent a direct CNS affect of HIV infection, and they called for a reconsideration of the relationship between apathy and cognitive impairment in HIV infection.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…While our findings and those from the laboratory of Bungener and Jouvent converge, further study is needed, including the use of more direct markers of CNS function (e.g., neuroimaging or CSF viral load). Further empirical scrutiny of these constructs may be particularly indicated given the findings of a recent study by Rabkin et al (2000), which failed to find an association between apathy and neurocognitive performance in a sample of HIV-infected subjects.…”
mentioning
confidence: 99%